A formal procedure for microwave power amplifier behavioral modeling - Pedro, J.C.
This work presents a formal behavioral modeling procedure for microwave power amplifier devices. By relying on the solid background of nonlinear system identification theory, a new behavioral model formulation was especially conceived to simplify the parameter set extraction from measurements made in a microwave laboratory. Indeed, the model now proposed is an optimal approximator of the real PA, for the nonlinear order considered, and is extracted, in a separable way, from measurements of the PA response when the device is excited by one of the easiest signals to generate in a RF laboratory: a multi-sine. © 2006 IEEE.